Implications of Public Understanding of COVID-19 in Saudi Arabia for Fostering Effective Communication Through Awareness Framework - Alanezi, Fahad; Aljahdali, Anan; Alyousef, Seham; Alrashed, Hebah; Alshaikh, Wyam; Mushcab, Hayat; Alanzi, Turki (Frontiers in Public Health, 2020)
Background: Participation of the public is an important and most effective approach for controlling the spread of novel coronavirus. However, considering its novel nature, it is important to create awareness among the public to be able to take timely preventive measures. On the contrary, misinformation and myths from online communities result in severe damages in mitigation of this novel disease. Objective: Focusing on these aspects, this manuscript reviews public awareness about COVID-19, myths surrounding it, its symptoms, treatment, transmission, importance of information sources, types of information to be considered in awareness campaigns, promotional channels, and their implications in Saudi Arabia. Methods: An online questionnaire-based survey was used for collecting data related to five major aspects related to COVID-19 and awareness creation process. The survey was accessed by 1,881 people, out of whom 741 people participated in the survey. However, 150 dropouts left the survey in between, as a result of which a final sample of 591 was achieved, indicating the response rate of 39.3% and a completion rate of 79.76%. Results: Awareness levels of the participants related to COVID-19, its means of transmission, preventive measures, symptoms, and treatment were identified to be moderate to high (60–80%). However, reliance on a few myths and violation of certain preventive measures were identified with majority of the participants (more than 60%). The Ministry of Health was identified to be the most reliable source of information followed by family and friends. Moreover, 15 types of information were identified to be highly relevant and important, which need to be effectively disseminated among the public through effective communication channels. Conclusions: Lack of awareness can result in serious outcomes in relation to COVID-19. Effective awareness campaigns including relevant information from reliable sources can improve the knowledge of people, and they must be effective in developing positive attitudes among the public toward adopting preventive measures.